DAMPAK INSTABILITAS INFLASI, BI RATE DAN KURS TERHADAP SUKU BUNGA PUAB 2009-2019 - Izza Aisha Rahmadiah (2021)
Economic Interbank Money Market Interest Rate is the reference interest rate used by banks and determined by the central bank for transactions in the money market in Indonesia. The interbank rate is influenced by various factors, including the inflation rate, the BI Rate and the exchange rate. This study aims to determine the effect of inflation, BI Rate and exchange rate on interbank money market interest rates. This study uses data from 2009 to 2019 per quarter. The method used in this study is a multiple linear regression analysis model using the OLS method. The results of multiple regression analysis show that (1) there is a significant effect between inflation on the PUAB Interest Rate (2) there is no significant effect between the BI Rate on the PUAB Interest Rate (3) there is a significant effect between the exchange rate on the PUAB Interest Rate.